2018
DOI: 10.21767/amj.2018.3435
|View full text |Cite
|
Sign up to set email alerts
|

Sources of information in health education: A cross-sectional study in Portuguese university students

Abstract: BackgroundLiteracy is a public health priority. The way people access health information is changing. It's crucial to understand this movement towards new communication tools, to better deal with it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 21 publications
0
16
0
2
Order By: Relevance
“…In the study by Schultes (62), various bachelor's degree programs were included and in the study by Sukys et al (63) different health study programs, except for medicine. In other three studies (48,60,64), no conclusion regarding general health literacy is given. Regarding eHealth literacy, authors of two studies (69, 70) speak of medium or higher scores based on a score of their measurement instrument, and the third study (68) made no statement regarding general eHealth literacy levels.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…In the study by Schultes (62), various bachelor's degree programs were included and in the study by Sukys et al (63) different health study programs, except for medicine. In other three studies (48,60,64), no conclusion regarding general health literacy is given. Regarding eHealth literacy, authors of two studies (69, 70) speak of medium or higher scores based on a score of their measurement instrument, and the third study (68) made no statement regarding general eHealth literacy levels.…”
Section: Resultsmentioning
confidence: 98%
“…According to the authors, accessible health services in the population and social understanding of health and disease and media distribution positively correlate with high health literacy levels. Santos et al (60) made no statement regarding overall health literacy due to their specific research question, but found the internet as a poor source for information gathering among students. Compared to the adult population of North-Rhine-Westphalia and the German general population, students surveyed by Schricker et al (61) have shown lower health literacy levels.…”
Section: Resultsmentioning
confidence: 99%
“…For the younger population, internet has substituted the classical media as the preferred source of mass information, with easily accessible and comprehensive content. However, internet is associated with lower literacy levels [ 17 ], because of the amount of fake information that is disseminated without technical review and appraisal [ 18 ]. Recent studies on digital health literacy about COVID-19 show that, although students generally achieve high levels, they are unable to make judgments about the reliability of online health information [ 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, real-time monitoring through electronic devices is a new way to make students taking sense of their current state, by assessing heart rate, for instance, sending an alert able to remind the need to change attitudes to decrease stress levels [ 43 ]. Information should be easily available in accessible sources, with scientific rigor and topicality [ 44 ].…”
Section: Discussionmentioning
confidence: 99%